Can tourism curb income inequality? Tourism Agenda 2030. Issue 2 (7th March 2023) - Seetanah, Boopen; Gopy-Ramdhany, Narvada; Bhattu-Babajee, Reena
Abstract : Purpose: This paper aims to examine the relationship between tourism development and income inequality, closely linked to the Sustainable Development Goals, for the case of a large sample of 83 countries (and subsamples) over the period 1990–2019. Design/methodology/approach: This study uses rigorous dynamic panel data analysis, namely, a Panel Vector Autoregressive Error Correction model, which takes into account both dynamic and endogenous relationships in the tourism-inequality nexus. Findings: The results provide strong support that tourism development has an income inequality reducing effect (albeit relatively small with a reported elasticity of 0.05). Subsamples analysis reveals that the impact of tourism on income inequality varies and is relatively larger in developing economies and those tourist-dependent economies, as compared to developed economies. In fact, it is reported that a 1% increase in tourism development reduces income inequality by 0.46% for developing and 0.56% for tourist-dependent economies as compared to only 0.02% in developed economies. It is further observed that tourism may affect income inequality indirectly via economic growth. Originality/value: This paper attempts to supplement the dearth literature on the tourism-inequality nexus by analyzing subsamples from a large data set while also using a dynamic panel data framework. The potential indirect effect of tourism on inequality via the economic growth channel is also explored. Abstract : 研究设计: 该研究采用了严格的动态面板数据分析, 即面板向量自回归误差修正模型（PVEM）, 该模型考虑到了旅游业不平等关系中的动态和内生关系。 研究目的: 本文以1990–2019年期间83个国家（及其子样本）的大样本为例, 研究旅游业发展与收入不平等之间的关系。 研究结果: 本研究结果证明, 旅游业发展具有减少收入差距的作用（尽管相对较小, 报告的弹性为0.05）。子样本分析显示, 与发达经济体相比, 旅游业对收入不平等的影响在发展中经济体和那些依赖游客的经济体中存在差异且相对较大。事实上, 据报道, 旅游业发展每增加1%, 发展中经济体的收入差距就会缩小0.46%, 依赖旅游的经济体会缩小0.56%, 而发达经济体的差距仅缩小0.02%。本研究进一步观察到, 旅游业可能通过经济增长间接影响收入差距。 原创性/价值: 本文试图通过分析大型数据集的子样本, 同时采用动态面板数据框架, 来补充关于旅游与不平等关系的文献的不足。本文还探讨了旅游业通过经济增长渠道对不平等的潜在间接影响。 Abstract : Diseño/metodología/enfoque: El estudio emplea un riguroso análisis dinámico de datos de panel, concretamente un modelo de corrección de errores autorregresivo vectorial de panel (PVEM), que tiene en cuenta tanto las relaciones dinámicas como las endógenas en el nexo turismo-desigualdad Objetivo: Este documento examina la relación entre el desarrollo del turismo y la desigualdad de ingresos, estrechamente vinculada a los Objetivos de Desarrollo Sostenible, para el caso de una amplia muestra de 83 países (y submuestras) durante el periodo 1990-2019. Conclusiones: Los resultados apoyan firmemente que el desarrollo turístico tiene un efecto reductor de la desigualdad de ingresos (aunque relativamente pequeño, con una elasticidad declarada de 0, 05). El análisis de submuestras revela que el impacto del turismo en la desigualdad de ingresos varía y es relativamente mayor en las economías en desarrollo y en aquellas economías dependientes del turismo, en comparación con las economías desarrolladas. De hecho, se informa de que un aumento del 1% en el desarrollo del turismo reduce la desigualdad de ingresos en un 0, 46% en las economías en desarrollo y en un 0, 56% en las economías dependientes del turismo, frente a sólo un 0, 02% en las economías desarrolladas. Se observa además que el turismo puede afectar indirectamente a la desigualdad de ingresos a través del crecimiento económico. Originalidad/valor: El artículo intenta complementar la escasa bibliografía sobre el nexo entre turismo y desigualdad analizando submuestras de un gran conjunto de datos y empleando un marco dinámico de datos de panel. También se explora el posible efecto indirecto del turismo sobre la desigualdad a través del canal del crecimiento económico.